Kualitas Asap Cair Terhadap Rekayasa Pipa Penghubung Kondensor - Noviadi , Tio; Gani , Maria Odelia ; Ridolf , Lady Dian ; Abrina Anggraini , Sinar Perbawani (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Many ways that can be done to preserve food, namely through the use of agricultural or biomass waste such as bamboo. Utilization can be used as a safe natural food preservative for the community. In order to obtain liquid smoke quality and safe to consume it is necessary engineering on condenser conduit pipes so that in this study need a performance test of condenser conduit pipe on pyrolysis reactor equipment. The purpose of this research is to determine the performance quality of long condenser conduit pipe on pyrolysis reactor device to liquid smoke quality. In this study, pyrolysis and purification process of liquid smoke from bamboo using pyrolysis reactor at optimum operating conditions where the length of condenser connecting pipes are used respectively 43 cm, 53 cm and 63 cm at 250 ?C for 1.5 hours. The results of this study show that the liquid smoke rendement obtained from each condenser connecting pipeline 43 cm, 53 cm and 63 cm is 19,5%; 19,24%; 17,55%, missing component is 40,54%; 41,68%; 47,62% and performance of pyrolysis reactor 453,49 g/h.m; 363,02 g/h.m; 278,57 g/h.m. The length of condenser connecting pipes having good pyrolysis reactor performance is 43 cm.